The Influence of National Interest in the Foreign Policy Outcomes in Malaysia During the Mahathir Era (1981 – 2003) - Syed Hamid, S. Jaafar Albar (AeU, 2015)
This paper explains the influence of National Interest (NI) in the formulation and execution of Foreign Policy (FP) of Malaysia during the Mahathir era since 1981-2003. Therefore, there is a need to analyse whether NI is the predominant factor influencing the FP of Malaysia and to indicate how strongly the NI and FP are related. However, the soundness of the application of the national interest and related theories are subjected to the degree of universality and flexibility of the changing geopolitical environment. These changing factors will be discussed in this paper via two objectives of study that leads to the establishment of two research questions. Two of the objectives of the study were; first, to indicate that the NI is the predominant factor in influencing the conduct of bilateral relations with other state actors and the participation in the multilateral framework and second, to identify the economic, political, security and societal interests and imperatives of Malaysia’s NI that drove the FP. The study adopted a qualitative methodology to interpret the events and episodes of FP of Malaysia during the Mahathir era. The findings showed that the use of events, objectives, postures, initiatives, strategies and implementation of the FP at the bilateral and multilateral domains on the questions of defence/ security, economic, societal interests and ideological values during Mahathir’s era was grounded by the NI - which went beyond the personality, character, family traits or educational background of Mahathir.